Investigating two solutions to balance revenues and N surplus in Swiss winter wheat. (August 2022) - Argento, F.; Liebisch, F.; Anken, T.; Walter, A.; El Benni, N.
Abstract: CONTEXT: Reducing N surplus from agriculture without compromising yield and quality requires economically and ecologically viable solutions. OBJECTIVE: Based on field data, we investigated a technical and market-based solution to balance the economic and environmental performance of nitrogen (N) fertilizer application in winter wheat in Switzerland. METHODS: The technical solution, i.e. variable rate (VR) technology, was compared to the standard uniform fertilizer application (ST) in terms of revenues and N balance over seven site-years between 2018 and 2020. The potential of a market-based solution to align revenues and N surplus was investigated based on the relationship between two indicators: the economic optimum (EO) of the revenues and the balanced N supply (BNS). The EO was estimated using a production function approach. The BNS was empirically defined as the point at which the N surplus estimated from total N input (N fertilizer + soil N supply) reaches a limit value of 30 kg N ha −1 . RESULTS AND CONCLUSIONS: On average, the revenues of VR were about 4% higher than in ST. The N surplus was, on average, 32% (21 kg N ha −1 ) lower in VR compared with ST due to a 13% reduction in N inputs with no significant differences in yield. Despite the differences across years and fields, VR appeared to be reducing N surplus without losses in revenues in 5 out of 7 site-years. The revenue curve reached an EO at total N input of 205, 249 and 246 kg N ha −1, in the years 2018, 2019, and 2020, respectively. The BNS was calculated at 220, 195, and 178 kg N ha −1  N inputs for the years 2018, 2019, and 2020, respectively. The results show that a price increase of up to 5.4 times the current fertilizer price through taxes would be necessary in order to reduce the N surplus to an environmentally friendly level. Such an increase would hardly be politically feasible. SIGNIFICANCE: The reported data showed that VR technology appears as a viable solution for producing lower N surplus at comparable revenue levels, thereby making it an option for small- to medium-scale winter wheat production in Switzerland. The environmental benefit could encourage the financial support of technologies for precise N management, which are often too expensive for these systems. Future research should verify or extend the numeric values found in this study. Graphical abstract: Unlabelled Image Highlights: A combined economic and ecological assessment of N fertilization showed possible solutions to reduce N surplus The technical solution, variable rate application, reduced N surplus by 32% without affecting revenues in 5 out of 7 fields The market-based solution, as tax on N price, was not viable to shift economic optimum toward a more balanced N supply